ANALISIS VISUAL KEMASAN BOTOL GOOD DAY PADA GAUL CREATION COMPETITION 2019 DENGAN TEMA “INDONESIA BANYAK RASA” - Audrey Lutfianti; Elda Franzia Jasjfi (Universitas Trisakti, 2023)
Abstract A Visual Analysis of The Good Day’s Bottle Packaging at Gaul Creation Competition 2019 With Theme “Indonesia Banyak Rasa”. Packaging becomes the initial attraction of a consumer in buying a product. Attracting consumers requires visual elements that match the company's image. It has been applied to the instant coffee-drink company good day through the creation competition for packaging design. This study will discuss visuals, especially the use of illustrations and colors in bottles of Good Day in Gaul Creation Competition 2019 with the theme